2011
DOI: 10.1121/1.3546097
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of signal coherence threshold and concealed spectral lines applied to detection of turbofan engine combustion noise

Abstract: Combustion noise from turbofan engines has become important, as the noise from sources like the fan and jet are reduced. An aligned and un-aligned coherence technique has been developed to determine a threshold level for the coherence and thereby help to separate the coherent combustion noise source from other noise sources measured with far-field microphones. This method is compared with a statistics based coherence threshold estimation method. In addition, the un-aligned coherence procedure at the same time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…The use of segment overlapping has potential to make MSC estimates even more precise; however, it also makes the analytical derivation of the MSC distribution very difficult to trace. In fact, for the special case of the MSC estimated between two signals, the explicit formula for the MSC statistical distribution is known only for the segmentation without overlapping; for the overlapped segmentation only approximations are available [23,33,34]. Still, for this MSC estimate, the analytic formula for the non-overlapped case has become a good basis for the approximation of the statistical distribution of the MSC estimated with segment overlapping.…”
Section: Future Workmentioning
confidence: 97%
“…The use of segment overlapping has potential to make MSC estimates even more precise; however, it also makes the analytical derivation of the MSC distribution very difficult to trace. In fact, for the special case of the MSC estimated between two signals, the explicit formula for the MSC statistical distribution is known only for the segmentation without overlapping; for the overlapped segmentation only approximations are available [23,33,34]. Still, for this MSC estimate, the analytic formula for the non-overlapped case has become a good basis for the approximation of the statistical distribution of the MSC estimated with segment overlapping.…”
Section: Future Workmentioning
confidence: 97%
“…Note that the higher statistical confidence interval based on the number of independent records (n d ¼ 128) is a more conservative estimate of the measured coherence threshold for the Honeywell TECH977 turbofan engine. Miles 13 previously found that with a 50 percent overlap the higher statistical confidence interval based on the number of independent records is a more conservative estimate of the measured coherence threshold for measurements made in the Pratt & Whitney PW4098 turbofan engine. Miles 13 showed that for a Gaussian distribution and using a 50 percent overlap to reduce the variance, a coherence threshold calculated with n o ¼ 2ns did work well.…”
Section: B Combustor-turbine Exit Acousticsmentioning
confidence: 97%
“…Miles 12,13 shows that instead of relying on the confidence interval given by Eq. (2), which is based on a statistical theory, to obtain a threshold value forĉ 2 nn ðn s Þ, one can use a deliberately unaligned time history to create the threshold value.…”
Section: B Combustor-turbine Exit Acousticsmentioning
confidence: 98%
See 2 more Smart Citations